Integrating Community Empowerment and Environmental Sustainability Through CSR: A Case Study of PT Sarihusada in The Upper Sleman Watershed, Yogyakarta - Aditya Romadloni; Febriyanti Angelia Ginting; Trisno Fallo; Putri Ratna Setyowati (Applied Environmental Sustainability and Technology, 2025)
The COMDEV and CSR program of PT Sarihusada Generasi Mahardika (SGM) in Padukuhan Kaliurang Timur, Kalurahan Hargobinangun, focuses on community empowerment and environmental curiosity. This research uses a descriptive qualitative approach to systematically describe various CSR initiatives carried out by PT SGM, by collecting data through program documentation, field observations, and participatory interviews. The CSR activities implemented include water conservation in upstream areas with the development of water catchment infrastructure, community-based integrated waste management, and urban farming as a strategy to improve food security. In addition, PT SGM also initiated the economic empowerment of women's groups through the Women Farmers Group (KWT) in dairy production and coffee harvest management. Environmental programs are enhanced through environmental education in elementary schools with the formation of environmental cadres and school garden management. To strengthen synergies, PT SGM also held multi-stakeholder discussions and campaigns to encourage cross-sector collaboration in preserving the environment. The whole program shows a holistic approach that combines ecological, economic, and educational aspects, and strengthens the community's capacity to face environmental challenges in a participatory and sustainable manner